Perbandingan Daun Kelapa Sawit (Elaeis guineensis Jacq.) dengan Daun Pandan (Pandanus amaryllifolius) dan Penambahan Jenis Madu pada Pembuatan Minuman Herbal - Nova Yulinar Saragih; Maria Ulfah; Sunardi (Program Studi Teknologi Hasil Pertanian, 2025)
This study aims to investigate the effect of the ratio of oil palm leaves to pandan leaves and the addition of different types of honey on the chemical and organoleptic characteristics of the resulting herbal drink, as well as to determine the best herbal drink formula. A Completely Randomized Block Design (CRBD) with two factors was used in this study. The first factor was the ratio of oil palm leaves to pandan leaves, consisting of three levels: (A1 = 70:30 w/w; A2 = 50:50 w/w; A3 = 30:70 w/w). The second factor was the addition of honey, with three types: (B1 = kapok honey; B2 = longan honey; B3 = forest honey). The results showed that the ratio of oil palm leaves to pandan leaves affected antioxidant activity, total phenolic content, total sugar content, and pH, but had no effect on color closeness based on chromameter tests, or the preference for color, taste, aroma, and appearance of the herbal drink. The addition of different types of honey affected antioxidant activity, total sugar content, and aroma preference, but had no effect on total phenolic content, pH, color closeness based on chromameter tests, or the preference for color, taste, and appearance of the herbal drink. The herbal drink with the highest antioxidant activity was produced at A1 (oil palm leaves to pandan leaves ratio = 70:30) and B3 (addition of forest honey), reaching 89.30%, with an average preference score of 4.78 (somewhat liked)